A GEOGRAPHIC INFORMATION SYSTEM (GIS) COFFEE SHOP DIKOTA JAMBI - Nurjani, Yeni; Hafsari, Andini (FORTECH (Journal of Information Technology), 2024)
A Geographic Information System (GIS) is an information system that can be used to provide information in the location search process. Therefore, in this research the author will discuss how to design and build an application that uses a geographical information system for cafe locations using a website-based application which aims to produce a location search application that can be used by users to find cafe information. This research was conducted to overcome problems for local visitors where visitors do not get information about scattered cafes, scattered locations are accessed online by searching via Google, the server will access the location of the cafe they want to visit.